Calcium Transport and Local Pool Regulate Polycystin-2 (TRPP2) Function in Human Syncytiotrophoblast - Cantero, Maria del Rocio (2013)
Polycystin-2 (PC2, TRPP2) is a Ca2+ -permeable, nonselective cation channel implicated in Ca2+ transport and epithelial cell signaling. Although PC2 may contribute to Ca2+ transport in human term placenta, the regulatory mechanisms associated with Ca2+ handling in this tissue are largely unknown. In this work we assessed the regulation by Ca2+ of PC2 channel function from a preparation of apical membranes of human syncytiotrophoblast (PC2hst) reconstituted in a lipid bilayer system. Addition of either EGTA or BAPTA to the cis hemi-chamber, representing the cytoplasmic domain of the channel, and lowering Ca2+ to ~0.6–0.8 nM, inhibited spontaneous PC2hst channel activity, with a time response dependent on the chelator tested. EGTA reduced PC2hst channel currents by 86%, with a t1/2 ¼ 3.6 min, whereas BAPTA rapidly and completely (100%) eliminated channel activity with a t1/2 ¼ 0.8 min. Subsequent titration with Ca2+ reversed the inhibition, which followed a Hill-type function with apparent dissociation constants of 1–5 nM, and 4 Ca2+ binding sites. The degree of inhibition by the cis Ca2+ chelator largely depended on increasing trans Ca2+. This was consistent with measurable Ca2+ transport through the channel, feeding the regulatory sites in the cytoplasmic domain. Interestingly, the reconstituted in vitro translated PC2 (PC2iv) was completely insensitive to Ca2+ regulation, suggesting that the regulatory sites are not intrinsic to the channel protein. Our findings demonstrate the presence of a Ca2+ microdomain largely accessible through the channel that controls PC2 function in human syncytiotrophoblast of term placenta.